2004
DOI: 10.1159/000078826
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Rhoa/Rho Kinase System in Flow-Related Remodeling of Rat Mesenteric Small Arteries in Vivo

Abstract: In small arteries, a chronic blood flow reduction leads to inward hypotrophic remodeling, while a chronic blood flow elevation induces outward hypertrophic remodeling. The RhoA/Rho kinase system was shown to be modulated by shear stress, and to be involved in other kinds of vascular remodeling. The aim of this study was to investigate the role of RhoA/Rho kinase in flow-related small artery remodeling. Rat mesenteric small arteries were subjected to flow-modifying surgery. After 1, 2, 4, 16, and 32 days, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…A first study has been performed in the model described in figure 1 using a cDNA microarray analysis (14 000 genes were analyzed). This analysis, confirmed by an Rt-PCR analysis showed an overexpression of RhoA and Rho kinase at day 4 after ligature followed a downregulation at day 16 and 32 91 . This is consistent with a role of the RhoA-Rho kinase system in high flow-induced remodeling.…”
Section: -Role Of Structure Proteins In the Adaptation Of The Microcsupporting
confidence: 61%
See 1 more Smart Citation
“…A first study has been performed in the model described in figure 1 using a cDNA microarray analysis (14 000 genes were analyzed). This analysis, confirmed by an Rt-PCR analysis showed an overexpression of RhoA and Rho kinase at day 4 after ligature followed a downregulation at day 16 and 32 91 . This is consistent with a role of the RhoA-Rho kinase system in high flow-induced remodeling.…”
Section: -Role Of Structure Proteins In the Adaptation Of The Microcsupporting
confidence: 61%
“…This is in agreement with previous studies showing that the RhoA/Rho-kinase pathway is involved in many cellular activities besides the cytoskeleton including vesicle trafficking, endocytosis, cellular differentiation and gene transcription (review: 92 ). Although the RhoA-Rho kinase system has a central role in cell function including pathways activated by shear stress, a treatment with the Rho-kinase inhibitor Fasudil failed to prevent or to reduce high flow-remodeling 91 , although the relatively low dose of fasudil used might not be high enough to block sufficiently the activity of the enzyme. In a model of chronic increase in flow in the pulmonary artery, a 10-fold higher dose of fasudil prevented arterial wall hypertrophy 93 .…”
Section: -Role Of Structure Proteins In the Adaptation Of The Microcmentioning
confidence: 99%
“…A chronic increase in blood flow has been reported by several groups to result in outward hypertrophic remodeling of resistance arteries (8,9,41,52,54,55,57). A widely used experimental animal model involves ligation of feed arteries in the mesenteric bed of rodents, whereby flow is shunted through adjacent parallel arcades.…”
Section: Flow-induced Vasodilatation and Flow-induced Remodeling Of Rmentioning
confidence: 99%
“…However, with techniques that are standard practice in single cell studies, a sufficiently large mRNA pool can be generated from isolated resistance arteries. Recently, using DNA microarrays after T7 RNA polymerase amplification of the extracted mRNA, we compared gene expression in rat mesenteric resistance arteries exposed for 1-32 days in vivo to normal or twice the normal blood flow in vivo (57). For a large fraction of the genes (Ͼ800 of 10,500), the expression was modified by more than twofold during exposure to altered blood flow in vivo.…”
Section: Differential Gene Expressionmentioning
confidence: 99%
“…Studies have demonstrated that a sudden increase in blood flow initiates an enlargement of the arterial lumen that progresses for months as the WSS tends to a homeostatic or normal level (23,25). A gradual increase in blood flow has been reported by several groups to result in outward hypertrophic remodeling of resistance (4,41,44,45,47) and conductive arteries (25,36,39). The flow-induced remodeling may be an attempt to maintain mechanical homeostasis (24,25).…”
mentioning
confidence: 99%